Assessing the technical efficiency of extensive livestock farming systems in Extremadura, Spain (Livestock Science, 2009)
The technical efficiencies of a sample of extensive dehesa farms were analyzed using a nonparametric Data Envelopment Analysis (DEA) model. This technique creates efficiency indices by comparing the performance of each farm with the best production practices observed, which define the efficiency or production frontier. The influence of the European Union's Common Agricultural Policy (CAP) subsidies (taken as an output) on the farms' efficiency was determined. The measurement of the efficiency has taken place from inputs per hectare thus allowing to make a different interpretation from the scale efficiency that, instead of referring to the dimension of the farm, is referred to the intensification. Thanks to the input-oriented analysis it can be established that the farms could maintain similar production levels by introducing a 30% reduction of their inputs (e.g. with breeds better adapted to the environment, a better use of the own produced pastures to reduce the amount of feedstuff to be bought, reductions in manpower…). Those highly intensified dehesas have shown decreasing inefficiencies of scale, whereas the least intensified have shown increasing inefficiencies. With a second stage analysis, different types of farms were identified as corresponding to greater or lesser efficiencies. It has been identified that the group of farms with high stocking rates have the greatest efficiencies indices. With respect to the livestock orientation, the farms with a livestock mix including pig were the most efficient. Modifications in the stocking rate, allowing an adequate use of the natural resources available, can be a solution to improve the efficiency of dehesa farms. In addition mixed livestock farming is another useful tool towards achieving increased efficiency, and a reduced dependence on subsidies.

Sustainability in Spanish Extensive Farms (Dehesas): An Economic and Management Indicator-Based Evaluation (Rangeland Ecology & Management, 2009)
The dehesa is defined as an agroforestry system that is characteristic of the southwestern Iberian Peninsula, where grassland is combined with evergreen species of the genus Quercus. Those systems have been gradually transformed from the Mediterranean forest into a unique kind of pastoral woodland by means of an agricultural use. Dehesas occupy more than 6 million ha, and the livestock systems that are based in them are of vital importance for their sustainability. The present work classifies, describes, and evaluates the sustainability of these systems in the Spanish region of Extremadura (southwestern Spain). To this end, we apply a methodological adaptation of the Framework for the Evaluation of Management Systems incorporating Sustainability Index (MESMIS). MESMIS is based on the evaluation of basic attributes of sustainability from indicators that allow one to make a simultaneous and comparative analysis of different types of farms. For the study, 69 farms were selected at random, and were classified using multivariate techniques into four types according to their level of intensification and productive orientation. The results were used to obtain an overall value of sustainability from a technical economic perspective for each farm type present in the dehesa. The mixed systems (beef cattle–sheep–Iberian pigs) have been found to be the most sustainable in general terms. The high–stocking rate sheep dehesas are the least sustainable, although at present, they are the most profitable. The other two groups analyzed, “low–stocking rate sheep farms” and “beef cattle farms,” had intermediate and similar scores. Mixed livestock dehesa farms are the closest to the traditional systems with a highly diverse production, an optimal use of the system's resources, and little dependence on external subsidies. In the present context, with uncertainties about European Union subsidies, this type of farm should be a goal for dehesa farmers.

Sheep farms in the Spanish rangelands (dehesas): Typologies according to livestock management and economic indicators (Small Ruminant Research, 2008)
Forty-six dehesa sheep farms of Extremadura (SW Spain) were analyzed on the basis of previously determined technical and economic indicators. A principal component analysis gave ﬁve principal components – related to intensiﬁcation, proﬁtability, and livestock mix – that characterized the farms. Using multivariate techniques based on these factors, a farm typology was established with six categories—three of sheep alone at different levels of intensiﬁcation, and three of sheep in combination with beef cattle or Iberian pig. This typology enabled homogeneous groups of farms to be considered for possible administrative actions relating to their optimal dimensions and stocking rates

Economic and management characterization of dehesa farms: implications for their sustainability (Agroforestry Systems, 2007)
Dehesa agroforestry systems occupy around 6 million ha in the Iberian Peninsula. Their economic and environmental sustainability depends on the maintenance of the extensive livestock farms which created this typical ecosystem. This work analyzes dehesa farms in the Extremadura region (SW Spain) using technical and economic indicators of 69 randomly selected holdings. Principal component analysis (PCA) allowed us to establish a valid model explaining 65.8% of the variance. The two principal components having most weight were Iberian pig production (explaining 20% of the variance of the model), and which ruminant species were raised on the farm (15% of the variance). A cluster analysis distinguished ﬁve types of farms: sheep farms at high and low stocking rates, beef cattle farms, wooded farms with mixed livestock, and farms with a high level of cropping activity. The most proﬁtable farms were those with either high overall livestock density or a high level of Iberian pig production. While high stocking density has historically attracted high levels of subsidy, production of Iberian pigs was proﬁtable because of the high value of the product. In the light of CAP reform, Iberian pig production seems the most readily sustainable type of farming for the dehesa system.

ANÁLISIS ECONÓMICO DE LAS EXPLOTACIONES EXTREMEÑAS DE DEHESA A TRAVÉS DE INDICADORES DE CAPITAL , COSTES , (Gestión Ambiental y Económica del Ecosistema Montado/Dehesa en la Península Ibérica, 2006)
En este trabajo se estudia la estructura técnico-económica de las explotaciones ganaderas de la dehesa extremeña, a través de indicadores técnicos y económicos. Se utiliza una metodología inspirada en la adaptación a nivel microeconómico del Sistema Europeo de Cuentas Económicas Integradas, aplicada a las cuentas económicas de la Agricultura y la Selvicultura. Los datos han sido obtenidos mediante la realización de encuestas a 76 titulares de explotaciones de dehesas de la Comunidad Autónoma de Extremadura realizadas durante los años 2004 y 2005. Las explotaciones estudiadas han sido fi ncas colaboradoras del proyecto “Desarrollo de un sistema de información para la gestión ambiental y eco- nómica del ecosistema dehesa/Montado en Extremadura y Alentejo”, fi nanciado por el INTERREG-III (SP4.E13).

Niveles de cargas ganaderas en la dehesa extremeña (Archivos de zootecnia, 2002)
This work analyzes the data collected from 143 sheep and/or cattle farms, representatives of the Extremaduran dehesa (semiarid grazing areas of the SW of Spain). A random survey was carried out in 2000, with an error of less than 5 percent and a confidence level of 95 percent. The aim of the survey was the evaluation of the stocking rate levels of these farms in 1999 and their evolution from 1993, first year after the CAP Reform of 1992. The effects of farm size for different stocking rates are studied. Significant differences were observed (p<0,05 and p<0,01) between the bigger and the lesser farm sizes. This shows a higher productive intensification when the grazing surface decreases. It is to mention a high correlation between the cattle units in sheep farms (UGMo) and the cattle units in the whole sample (UGMt) (r=0,867; p<0,01), as well as the association between sheep density and pig density variables (r=0,773; p<0,01). On the other hand, we can observe an inverse correlation between the levels of livestock density and the farm size, which is more significant in cattle farms.

Tipología de sistemas adehesados* (Archivos de Zootecnia, 2001)
This work analyzes a a group of livestock farms in semiarid grazing areas in Spain. The surface sample studied adds up to 80.000 hectares. The results are expressed according to the livestock prevalence of the farms. INTRODUCCIÓN